Anticancer agent FTY720 upregulates cell cycle regulator BTG2 via the SET/TAF-Iβ –PP2A–SMAD3 signaling pathway and induces G2/M arrest in leukemia - Jieun Park; Yugyeong Kim; Hyebin Park; Geonhui Yun; Sang Beom Seo (Genes & Genomics, 2026)

Seasonal interplay of water mass mixing and nutrient dynamics in an Arctic fjord: a case study of Kongsfjorden, Svalbard - Hyebin Kim; Dukki Han; Sang Rul Park; Tae-Hoon Kim (Ocean Science, 2025)
This study examined seasonal variations in water mass structure and nutrient dynamics in Kongsfjorden, a high Arctic fjord where water mass composition varies seasonally due to mixing among Atlantic Water, Polar Surface Water, and glacial meltwater. In spring, the dominance of Modified Atlantic Water (MAW) facilitated active vertical mixing, leading to relatively high, uniform nutrient concentrations throughout the water column. In summer, the enhanced influence of glacial meltwater and warmer Polar Surface Waters (PSWw) resulted in strong surface stratification and significant nutrient depletion in the upper layer. To disentangle the effects of physical mixing from biological consumption, theoretical nutrient concentrations were calculated based on a four-component water mass mixing model. The positive differences between theoretical and observed concentrations (ΔNutrient) were indicative of significant biological uptake, which accounted for substantial nutrient reductions in observed surface concentrations from spring to summer: approximately 69 ± 18 % for NOx (sum of nitrate and nitrite; NO3- + NO2-), 74 ± 15 % for phosphate, and 47 ± 18 % for silicate. Crucially, ΔNutrient values served as a “biogeochemical memory”, reflecting the cumulative net biological consumption since the spring bloom rather than just instantaneous phytoplankton biomass. These biological processes also altered nutrient stoichiometry, as reflected by an increase in the surface dissolved inorganic nitrogen to phosphorus (DIN/DIP) ratio (DIN = NO2? + NO3- + NH4+; DIP = PO43-) from 15.0 in spring to 18.8 in summer, indicating a shift in nutrient limitation patterns. Consequently, summer surface waters transitioned toward potential co-limitation, with concentrations of phosphate (∼ 0.13 ± 0.07 µM) and silicate (∼ 1.66 ± 0.39 µM) approaching their respective limitation thresholds. These findings highlight a clear seasonal transition from a physically controlled, nutrient-replete spring to a biologically regulated, nutrient-limited summer. This understanding is crucial for predicting how Arctic fjord ecosystems, and their primary productivity, will respond to ongoing Atlantification and increased freshwater input under climate change.

In vitro selection of a trans aptamer complex for target-responsive fluorescence activation - Soyeon V. Park; Byunghwa Kang; Minjong Lee; Hyebin Yoo; Hyesung Jo; Sungwook Woo; Seung Soo Oh (Analytica Chimica Acta, 2024)

Proteomics Reveals Plasma Biomarkers for Ischemic Stroke Related to the Coagulation Cascade - Jiyeong Lee; Sora Mun; Arum Park; Doojin Kim; Yoo-Jin Lee; Hyo-Jin Kim; Hyebin Choi; Miji Shin; Soo Joo Lee; Jae Guk Kim; Yeon Tae Chun; Hee-Gyoo Kang (Journal of Molecular Neuroscience, 2020)